Approaches to Increase the Cultural Capital Potential to Promote Community Product Development: A Case Study of the Lad Yai Herbal Salt Community Enterprise in Samut Songkhram Province - Kitipadung, Jitsupa; Jaiborisudhi, Watunyu (Rajapark Journal, 2021)
The purposes of this study were to analyze the cultural capital potential of the Lad Yai Herbal Salt Community Enterprise in Samut Songkhram province of Thailand and present an approach to develop the products created from cultural capital accumulated within the Lad Yai community. This qualitative research was gathered data from a literature review, in-depth interviews, and a focus group selected from a sample of representatives who have the potential to develop cultural capital. It was found that the internal capital of the enterprise is well ready, but what requires the most urgent support is marketing. Concerning approaches to develop their products, the enterprise should diversify their products and make them appropriate for daily usage. This research also suggested integrating the selling points of the cultural capital of salt farming into the community products and applying this identity to increase demand and add value.